The relationship between running performance in the Olympic-distance triathlon and aerobic physiological variables, focusing on the 3 factors of the classic model - Aoyagi, A.; Ishikura, K.; Shirai, Y.; Nabekura, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2020)
The 3 factors of the classic model (maximal oxygen uptake [VO2max], fractional utilization of VO2max at the anaerobic threshold, and running economy [RE]) are well known to be the determinants of isolated distance running performance. However, no previous studies appear to have investigated the relationship between all 3 factors and running performance in the Olympic-distance triathlon (ODT). We therefore investigated this relationship by conducting 2 studies. In study I, the relationship between the 3 factors of the classic model and running performance in actual ODT races was investigated in 16 male triathletes. In study II, the relationship between the three factors and running performance in simulated ODT races with controlled exercise intensities, pedaling cadence, and carbohydrate intake during the swim and bike legs was investigated in 8 male triathletes. The 3 factors were quantified using a treadmill incremental test following the same protocol in each study. Simple correlation and multiple regression analyses were performed using the forced entry method. The independent variables were the 3 factors of the classic model, and the dependent variable was running performance in the ODT races. In study I, no significant correlation was found between the 2 measurements (p > 0.05). Furthermore, no significant multiple correlation coefficient was obtained (R < 0.54, p > 0.05), and < 10.7% of the running performance was attributable to the 3 factors. In study II, by contrast, a significant correlation was found between RE and running performance (r = 0.79, p = 0.02). In addition, a significant multiple correlation coefficient was obtained (R = 0.91, p = 0.05), and 69.9% of the running performance in the simulated ODT race was attributable to the three factors. In conclusion, we suggest that in the ODT the 3 factors of the classic model explain interindividual variation in running performance. However, in an actual ODT race, the relationship between the 3 factors and running performance may weaken owing to the residual effects of prior swimming and cycling.